Impactos econômicos e sociais de inundações em bacia hidrográfica urbana - LEONARDO DE SOUZA BRUNO (2021)
Floods are among the classes of natural disasters that cause the most damage values in human activities around the world. Together with this, it appears that the risk of occurrence of floods is growing, especially in urban areas, due to factors such as climate change, rapid urbanization, and occupation of irregular and dangerous areas. Therefore, we need to know the areas that can potentially be affected by flood, as well as delineate methodologies to determine the damage that these events can cause, both financial and social. To discover areas at risk, computational modeling is a powerful tool, however, simulations in small urban watercourses represent a challenge, given the complexity of urban drainage systems, which requires high resolution data. Thus, in chapter 2 of this dissertation, we applied the coupled models HEC-HMS and HEC-RAS to determine flood areas in the Prosa stream basin, in Campo Grande, Brazil. In this, we use sub-hourly hydrometeorological data in addition to terrain models with 1 meter resolution, along with bathymetric data. When analyzing actual and design rainfall-based events, metric data models in calibration and validation, values of R² = 0.93, RMSE = 1.29 and NSE = 0.92 for HEC-HMS, and values of R² = 0.93, RMSE = 1.29 and NSE = 0.92 for the HEC-RAS. The results encourage the application of these models to flood studies in urban areas. Regarding the quantification of potential economic damages, in chapter 3 we apply quota curves versus losses (generated for Brazil), as well as discuss about the dynamics of the flooding process in the Prosa basin. The results show that floods with a return time equal to 100 years can cause damages of up to 500,000 US dollars, however, the data do not have a good correlation with the real elements in the Prosa basin. We've found that flood protection measures work, but the solution to floods depends on many other factors. Decision makers can use the results and methodology of these chapters to analyze flood events in other urban areas.